Forecasting Omset Printing of Printing Sales in CV Sembilan Jaya with Neural Network Method - Reni Vivit Ayu Mawarti; Wiwiet Herulambang; R Dimas Adityo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
Forecasting is a process for estimating several needs in the future which includes needs in order to meet thedemand for goods and services. Neural Network Backpropagation Method is a time series forecasting method. Thepurpose of this study is to predict the turnover results in the next period obtained by CV. Nine Jaya every week. Thisstudy uses sales data obtained from the printing of food boxes, shoe boxes, watch boxes from January 2014 toDecember 2018. The results of this forecasting are done using the Neural Network method, the smallest MSE valueobtained is 0.004211 with 1000 times iteration and learning rate 0.2. The MSE value obtained meets the condition orcondition value as a good forecasting method because it is able to meet the MSE value requirement <0.1.